Study of cases of head injury in a government hospital in rural Indian setting - Pusdekar, Vinod; Ambedkar, Sandeep; Bodade, Ritesh (International Surgery Journal, 2018)
Background: Head injury can be defined as trauma in which the head is struck or moves violently, resulting in transient or permanent alteration of consciousness of an individual. We profiled and analyzed the cases of head injuries reporting to a government hospital a rural Indian setting. Methods: All the patients with history of antecedent head injury were firstly assessed by detailed history, with emphasis on history of unconsciousness/vomiting/convulsions/ENT bleed. Then a thorough clinical examination was undertaken, including Glasgow Coma Scale (GCS) scoring. Further, all the patients were subjected to CT scan of head for correlation of clinical findings, confirmation of diagnosis, delineation of extent of disease and suitability of operative intervention etc. Results: Majority of the patients belonged to 15-44 years age group (30, 60%) and were males (38, 76%). Road traffic accidents accounted for majority (38, 76%) of the cases. GCS score was found to range between 13-15 (mild) in 18 (36%) patients, 9-12 (moderate) in 21 (42%) patients and 3-8 (severe) in 11 (22%) patients. Best recovery (88%) was shown by patients of GCS score between 13-15. Among the critical symptoms and signs, unconsciousness and abnormal plantar reflex were the commonest ones. Generalized cerebral edema without associated lesion (50%) was the commonest finding followed by extradural hematoma (EDH) (40%) on CT scan of head. As for recovery w.r.t. CT scan findings, highest rate of recovery (100%) was reported in patients with fracture without intracranial pathology, while highest mortality was reported in those having mixed lesion (90%). Conclusions: Road traffic accidents in young age group is the commonest mode of head injury and GCS score is a good predictor of recovery in head injury cases.